Hubungan pola makan pendamping ASI dengan pertumbuhan dan perkembangan gerak motorik kasar bayi 6 – 12 bulan di Kecamatan Bermani Ulu Kabupaten Rejang Lebong - Antoni Herwan; Toto Castro; Ita Paramastri (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2005)
Background: The main problem facing Indonesian people today is nutrition deficiency which brings effect to low quality of human resources. Infants aging 6 – 12 months are at high risk of having growth and development disorder. Complementary breastfeeding pattern is one of factors causing gross motoric movement growth and development disorder.Objective: This study was meant to know the relationship be-tween complementary breastfeeding pattern and gross motoric movement growth and development of infants aging 6 – 12 months at Bermani Ulu Sub district, Rejang Lebong District.Method: This was observational type of research which used cohort design. The samples consisted of 87 infants of 6 – 12 months selected through simple random sampling. Complementary breastfeeding pattern data were collected using interview and food call methods, growth data using anthropometry measurement, gross motoric movement data using motoric guideline of infants aging 3 – 18 months. Analysis of data used chi-square, anova, logistic linier and logistic regression.Results: The result of the study showed there was no significant relationship (p>0.05) between complementary breastfeeding pattern and gross motoric movement growth and development. There was significant relationship (p<0.05) between energy intake and protein intake and growth, with energy intake and protein intake. There was significant relationship (p<0.05) between energy intake and protein intake and development, with energy intake and protein intake. Result of multivariate analysis showed there were 2 variables as growth predictor i.e. energy intake (B=0.096) and protein intake (B=0.351) with (24.7) R square and there were 2 variables as gross motoric movement development predictor i.e. energy intake and protein intake (p<0.05).Conclusions: 1) Complementary breastfeeding were not related to gross motoric movement growth and development, 2) energy and protein intake of complementary breastfeeding were related to gross motoric movement growth and development, 3) energy and protein intake were dominant factor which were related to gross motoric movement growth and development.